ROLE OF KRIYAKALPA IN THE MANAGEMENT OF NETRA ROGAS - Anjaneya Prasad, Nandam; Anil Kumar, *Singh; Akhilnath, Parida; Kalanidhi, Hota; Dr, Ashu (International Journal of Ayurveda and Pharma Research, 2017)
The promotion of the visual acuity was considered as one of the priorities in the branch of Shalakya tantra of Ayurveda. Many procedures and formulations have been described to cure the ophthalmic disorders. Present conventional system of medicine has topical and systemic administration of drugs to the eye which are highly inefficient and there is a need for controlled, sustained release, particularly for conditions that affect all parts of the eye. Sushruta, the father of ancient Indian surgery, advocated Kriyakalpa is the main therapeutic procedure for Netra Rogas, along with other forms of treatment. He has described this in a separate chapter in Uttartantra of Sushruta Samhita. Some of the proven principles of management procedures and medicaments include intake of purified medicated ghee (Ghritapaana), nourishing eye bath therapy (Tarpana), and processed liquid instillation through nostrils by drops or powders (Nasya), eye bath therapy (Pariseka), application of medicated paste on eye lids (Bidalaka) and collyrium (Anjana). These procedures improve the vision by strengthening of the cilliary muscles, maintaining unctuousness of the eye ball, proper accommodation of the lens, delays the senile opacity of the lens etc. On the other hand these procedures also helpful in dealing with inflammatory conditions like conjunctivitis, hordeolum, corneal ulcer, staphylloma, panopthalmitis etc. Thus Kriyakalpa can be done in healthy as well as diseased eye conditions to improve the ophthalmic health.